The evolution of co-opetition in the Waipara wine cluster of New Zealand - Léo Paul Dana; Julien Granata; Frank C. Lasch; Alan Carnaby (Wine Economics and Policy, 2013)
The co-opetition literature has long focused on the explanatory variables for competitors engaging in cooperative relationships. Yet, there is a gap in understanding the evolution of coopetition. In this article, we re-visit an embryonic cluster in New Zealand and investigate changes over time. The paper examines a regional wine cluster against a background of industry restructuring, competition and internationalization. The study thus contributes to our understanding of the evolution of a regional wine cluster and its implications for wine business. The originality of the paper is twofold:first, the paper uses the co-opetition approach to provide a better understanding of cooperation and competition in clusters; second, the area of observation is located in a market that literature qualifies (from a European viewpoint) as new world wine. The paper notes the growing importance of glocal perspectives in business and economic development. A point often neglected in contemporary research, we emphasise that geography and location matters for management and economic research.
Keywords: 330; Cluster; Co-opetition; Competition; Cooperation; Evolution; France; Wine sector